The Relationship Between Knowledge about Flood Disasters and Community Preparedness in RW 34, Bojongkulur Village, Bogor Regency - Sitorus, Seven; Silalahi, Martha K.; Surwaningsih; Wijaya , Alicia Salma (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Background: Flooding is the occurrence of a significant increase in river water flow volume from normal conditions due to continuous rain falling in the upstream area or in certain areas. Flooding is a significant increase in river water flow from normal conditions due to continuous rain, where this often causes a great risk due to the lack of public knowledge about preparedness in facing flood disasters. The purpose of this study was to determine the relationship between knowledge about flood disasters and community preparedness in RW 34, Bojongkulur sub-district, Bogor district. Method: This study uses a quantitative design with an observational analytical method through a cross-sectional approach. The sample in this study was 116 people in RW 34, Bojongkulur sub-district. The instrument in this study was a questionnaire sheet with data analysis using the chi-square test. Results: The results of this study indicate that there is a relationship between knowledge about disasters and community preparedness with a p value of 0.029 (p < 0.05). Of the 116 respondents with good knowledge, more had very good preparedness (78.7%) compared to those with very poor preparedness (21.3%). Conclusion: Respondents with good knowledge have good preparedness. There is a significant relationship between the level of knowledge about flood disasters and community preparedness. The higher a person's level of knowledge, the better their preparedness in facing flood disasters.